Jezikovno-vedenjski vzorci opravičevanja v slovenščini - Krajnc Ivič, Mira (Slavistična revija, 2010)
The article aims to show, on the selected material of linguistic (and behavioral) patterns, a multi- functionality of dialogic acts as one of the basic suppositions for creating coherence in the dialogue. This should shed light on the inappropriate understanding of the apology as an act in which a merely phatic function is dominant.
Keywords: discourse; diskurz; dvogovor; opravičevanje; Slovene; slovenščina; vedenjski vzorci